Pengaruh Profitabilitas, Likuiditas, Dan Leverage Terhadap Nilai Perusahaan (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2022 - Nicholas Ricky Hansel Ardhana; Dyah Ratnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research to analyze and prove the effect of profitability, liquidity, and leverage on firm value. The research focuses in industrial sector manufacturing companies that are listed on the Indonesia Stock Exchange from 2019 to 2022 period. The sample of this research were chosen through the purposive sampling technique and resulting 11 sample companies. The data were analyzed using multiple linier regression and using SPSS software version 26. The result showed that profitability, liquidity, and leverage have a significant positive effect on firm value. This research underscores the importance of companies to maintain and increase profitability. High profitability indicates the company's ability to generate profits and use assets efficiently, ensure adequate availability of current assets, find the right balance between debt and equity to maximize firm value.